2013
DOI: 10.1037/a0034487
|View full text |Cite
|
Sign up to set email alerts
|

The relation between symptoms of bulimia nervosa and obsessive-compulsive disorder: A startle investigation.

Abstract: Bulimia nervosa (BN) and obsessive-compulsive disorder (OCD) co-occur at greater rates than chance and may have shared mechanisms of dysfunction. One of these proposed mechanisms is a hyper-responsive aversive system as indicated by heightened startle response to aversive stimuli. The present study examined this hypothesis using 2 types of aversive stimuli: disorder specific (e.g., high-caloric food pictures for BN, contamination pictures for OCD) and nondisorder specific (e.g., knife). Temporal parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(94 reference statements)
0
8
1
Order By: Relevance
“…This finding suggests that the cognitive concerns characteristic of eating disorders is related to appraising food as negative while viewing it. In contrast to some past research (Altman, Campbell, Nelson, & Shankman, ; Drobes et al, ; Mauler et al, ), we did not find an association between startle blink modulation and eating disorder cognitions or behaviours, suggesting that defensive motivational responding to food did not characterize individuals with high eating disorder concerns. Taken together, the aversive nature of food appears to be expressed at the cognitive level rather than the basic motivational level in this sample.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding suggests that the cognitive concerns characteristic of eating disorders is related to appraising food as negative while viewing it. In contrast to some past research (Altman, Campbell, Nelson, & Shankman, ; Drobes et al, ; Mauler et al, ), we did not find an association between startle blink modulation and eating disorder cognitions or behaviours, suggesting that defensive motivational responding to food did not characterize individuals with high eating disorder concerns. Taken together, the aversive nature of food appears to be expressed at the cognitive level rather than the basic motivational level in this sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Behavioural studies have demonstrated that people with PTSD, OCD, and ED show anomalies in physiological response to threat. For example, there is an exaggerated physiological startle response to anticipation and viewing of disorder-specific, potentially threatening stimuli, such as images of trauma, contamination, or food (Altman et al, 2013;Mauler et al, 2006;Pitman et al, 2012;Simon et al, 2013). Additionally, a number of reviews have reported atypical attentional bias towards disorder specific stimuli (Bar-Haim et al, 2007;Brooks et al, 2011;Cisler and Koster, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Both image types were associated with potentiated startle responses, relative to neutral images, as well as non-significant differences in startle responses on maintain and suppress regulation trials. Despite one conflicting result (Friederich et al, 2006), most studies examining clinical and analog samples of women with BN also report potentiated startle responses to food images (Altman et al, 2013, Drobes et al, 2001, Mauler et al, 2006), suggesting implicit emotional reactivity to food is disturbed across eating disorders. In contrast, healthy control participants typically experience startle inhibition when viewing food images in non-deprived states (Drobes et al, 2001, Ferreira de SĂĄ et al, 2014, Mauler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%